Homeotic genes and the regulation of myoblast migration, fusion, and fibre-specific gene expression during adult myogenesis in Drosophila. - Roy, S.; VijayRaghavan, K. (Development, 1997)
We have investigated the roles of homeotic selector genes in the migration and fusion of myoblasts, and in the differentiation of adult muscle fibres of Drosophila. Altering intrinsic homeotic identities of myoblasts does not affect their segment-specific migration patterns. By transplanting meso - and metathoracic myoblasts into the abdomen, we demonstrate that the fusion abilities of myoblasts are independent of their segmental identities. However, transplanted thoracic myoblast nuclei are 'entrained' by those of the host abdominal muscles to which they fuse and are unable to 'switch on' a thoracic muscle-specific reporter gene. This process is likely to be mediated by homeotic repression because mis-expression of an abdominal muscle-specific homeotic gene, Ultrabithorax, in the thoracic muscles results in the repression of the thoracic muscle-specific reporter gene. Finally, we show that removal of Ultrabithorax function specifically from muscle cells of the first abdominal segment, results in the expression of thoracic muscle properties. Many of these functions of homeotic genes in muscle patterning in Drosophila could be conserved during myogenesis in other organisms.